1990
DOI: 10.1093/clinchem/36.3.562
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced proteinuria in well-trained athletes

Abstract: We studied the rate of urinary excretion of albumin, alpha 1-microglobulin (as an indicator of the renal tubular involvement), sodium, potassium, and creatinine in the basal state (overnight urine collection) and after physical exercise (training session) in 10 professional cyclists, to verify whether protein excretion is increased even in well-trained athletes after physical effort. In addition, we wanted to understand whether the origin of exercise-induced proteinuria was glomerular, tubular, or both. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 12 publications
(8 reference statements)
0
5
2
2
Order By: Relevance
“…In line with the present study, they observed that creatinine excretion increased after physical activity. These results were inconsistent with those of the research conducted by Rasm et al (1974), William (1970), Clerico (1990), and Poortmans (1978). It seems that difference can be due to differences between football field and other sports and differences between Football players and other sports players in terms of physical pressure imposed on athletes and exercise pressures.…”
Section: Discussioncontrasting
confidence: 74%
“…In line with the present study, they observed that creatinine excretion increased after physical activity. These results were inconsistent with those of the research conducted by Rasm et al (1974), William (1970), Clerico (1990), and Poortmans (1978). It seems that difference can be due to differences between football field and other sports and differences between Football players and other sports players in terms of physical pressure imposed on athletes and exercise pressures.…”
Section: Discussioncontrasting
confidence: 74%
“…Changes in albuminuria over time, however, can also be the result of other factors not related to drug intervention. It is well known that albuminuria shows a substantial within‐individual day‐to‐day variability that can be attributed to physical activity , analytical factors, measurement variability , posture or fever . These daily fluctuations hamper the accuracy of drug efficacy monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Albuminuria, a type of Proteinuria, was shown in all athletes after exercise that was due to the increased need for protein in athletes. While the proteinuria was directly related to the severity of exercise 22 . In a study by Kohanpour in 2002, which was aimed to investigate the effect of the intensity of aerobic activity on proteinuria in young soccer players, a sharp rise in urine albumin was shown immediately after exercise, followed by decrease in about 45 minutes later, but not to normal level (25).…”
Section: Discussionmentioning
confidence: 95%